EFFECT OF TREE MARIGOLD (Tithonia diversifolia (HEMSL.) A. GRAY) LEAVES INFUSION AND ETHANOL EXTRACT ON BLOOD GLUCOSE LEVEL AND LIVER HISTOPATHOLOGY OF STREPTOZOTOCIN-INDUCED MALE WISTAR RATS - Rachma Ayu Maulidiany; Eni Suhaeni; Catur Setiya Sulistiyana; Ariestya Indah Permata Sari (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Common Indonesians often use alternative therapy for Diabetes Mellitus (DM) due to its high prevalence. Tree marigold (Tithonia difersivolia (Hemsl.) A. Gray) leaves show its positive effect in decreasing blood glucose level. Thus, it is important to analyze the negative effect of consuming the proposing alternative including its toxicity level to vital organs. This study aims to observe the blood glucose level and liver histopathology in streptozotocin-induced diabetic male rats treated by infusion and ethanol extract of the tree marigold leaves. Methods: Pretest and posttest with control group design experiment was conducted to analyze effect on blood glucose level and posttest only with control group design was for determining liver histopathology. Twenty-four male white rats (Wistar strain) were randomly divided into 4 groups: normal control group (KN), positive control group (K+) treated with 0.45mg/kg of glibenclamid, treatment group 1 (P1) treated by 100 mg/kg of tree marigold leaves ethanol extract, and treatment group 2 (P2) treated by 1373 mg/kg of tree marigold leaves infusion. The rats at the groups of K+, P1, and P2 were induced by streptozotocin to reach hyperglycemic state. Comparison of blood glucose level effect between infusion and ethanol extract was analyzed by One-Way ANOVA continued by post-hoc test, while comparison of liver histopathology effect was determined by Kruskal-Wallis continued by Mann-Whitney test. Results: Significant differences of blood glucose level decrease were found in all groups. Group P2 significantly decreased blood glucose level more than P1 (p=0.000) as much as 124.97 mg/dl and 101.46 mg/dl respectively. Significant differences of liver histopathology were obtained between KN vs K(+), KN vs P2, K(+) vs P2, and P1 vs P2. Group P2 showed more severe of liver histopathology changes than P1 (p=0.025). Conclusion: Tree marigold leaves extract is more effective in lowering blood glucose level and has less toxic effect to liver histopathology than its infusion.